2017
DOI: 10.1038/sc.2017.49
|View full text |Cite
|
Sign up to set email alerts
|

Validity of one-repetition maximum predictive equations in men with spinal cord injury

Abstract: All 1RM predictive equations are accurate to assess individuals with SCI at the bench press exercise. However, the predictive equation of Lombardi presented the best associated cross-validity results. A specific 1RM prediction equation was also elaborated for individuals with SCI. The created equation should be tested in order to verify whether it presents better accuracy than the current ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Before the 1RM test, subjects performed a warm-up of 5-10 repetitions with 50% of the perceived maximum load. After 1 minute of rest, 3 to 5 repetitions with 70% of the perceived maximum load were performed (5,8,11,18,21). The perceived maximum load was estimated based on the researcher and subject perceptions related to usual weights performed during para powerlifting training sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Before the 1RM test, subjects performed a warm-up of 5-10 repetitions with 50% of the perceived maximum load. After 1 minute of rest, 3 to 5 repetitions with 70% of the perceived maximum load were performed (5,8,11,18,21). The perceived maximum load was estimated based on the researcher and subject perceptions related to usual weights performed during para powerlifting training sessions.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure is most interesting if participants are not able to move the maximal weight for one single repetition due to health-related reasons or limited muscle coordination—a typical situation for people with SCIs during primary rehabilitation. It has been shown that based on the indirect determination of the 1RM, reliable information concerning maximal strength in individuals with SCIs can be obtained [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with those observed in the studies of Loturco et al [ 38 ] and Iturricastillo et al [ 10 ], where the association between the MPV and the %1RM was also high in the free execution mode in BP exercise (R 2 = 0.95 and R 2 = 0.94 for Loturco et al [ 38 ] and Iturricastillo et al [ 10 ], respectively). Bearing in mind that performing a complete and standardized test protocol to determine the 1RM in team sports requires a lot of time and has a high risk of injury [ 38 , 39 ], and taking into account the high association found in this study, coaches and physical trainers of WB teams could use both the MPV and the V max to estimate the %1RM of their players. Currently, there are different valid and reliable tools to measure the velocity of execution of an exercise; so, to obtain these data is not complicated [ 11 ].…”
Section: Discussionmentioning
confidence: 99%